Implementation of Video Demonstration of Foodstuffs Chop in Direct Learning Setting for Vocational High Schools Students - Yulinda Ariska Mela Putri; Mauren Gita Miranti; Sri Handajani; Niken Purwidiani (PT ARRUS Intelektual Indonesia, 2023)
Video demonstrations are applied corresponding to direct learning and provide support for students to have complete knowledge that requires repetition in the domination of the concept. This study analyzes the influence of implementing video demonstrations in the direct learning setting of foodstuffs chop on the knowledge level and the performance level learning outcomes. Forty students of the 11th culinary class at SMKN 1 Cerme Gresik were involved in this quantitative study using a pretest-posttest design. This study employed observation and test methods using observation sheets of learning implementation, performance observation sheets, and multiple-choice test questions. Data were analyzed using the SPSS 25.0 program to answer the proposed hypothesis. The SPSS output shows a significance of .000 <.05, which shows that the application of video demonstrations of foodstuffs chop in direct learning settings has a significant effect on learning outcomes at the level of knowledge. Meanwhile, the SPSS output for performance level learning outcomes shows .000 <.05, it shows that the application of video demonstrations of foodstuffs chop in direct learning settings has a significant effect on performance level learning outcomes. This study recommends using other demonstration videos, such as animated videos, and live videos to find out the effectiveness of each and the teacher can choose the most effective demonstration videos.